ANALISIS PERILAKU ONLINE IMPULSIVE BUYING: SHOPPING LIFESTYLE, SALES PROMOTION, HEDONIC SHOPPING MOTIVATION DAN PAY LATER - Pertiwi, Dian; Wibowo, Bambang Setia (Jurnal Ekonomi Dan Bisnis, 2022)
This study aims to examine the effect of Shopping Lifestyle, Sales Promotion, Hedonic Shopping Motivation and Pay later on online impulsive buying behavior. This research used a survey design with purposive sampling. In this study, it used a quantitative approach with a sample of 144 Shopee consumers and using Shopee pay later when making transactions. The data source used is primary data using questionnaires. The data analysis method used is multiple linear regression analysis. Based on the results of the study: (1) there is a positive influence of shopping lifestyle on impulsive buying (2) there is no positive influence of sales promotion on impulsive buying (3) there is no positive influence of hedonic shopping motivation on impulsive buying (4) there is a positive influence of pay later on impulsive buying.